Large magnetocaloric effect in free-standing Gd2O3 nanostructures near liquid helium boiling point - S Hazarika; D Mohanta; A V Morozkin; R Nirmala (Materials Research Express)
Magnetic and magnetocaloric properties of free-standing gadolinium oxide (Gd _2 O _3 ) nanostructures have been studied. Nanoparticles of Gd _2 O _3 (Gd _2 O _3 -NP), nanorods of Gd _2 O _3 (Gd _2 O _3 -NR) and a mixed system of Gd _2 O _3 nanosheets and nanorods (Gd _2 O _3 -NS+NR) have been prepared by template-free methods without the use of any surfactant or a catalyst. These samples crystallize in cubic crystal structure (space group Ia- 3, no. 206, cI 80). Magnetization data indicate typical paramagnetic behavior in the temperature range of 300 K to 5 K for all the samples. All three Gd _2 O _3 nanostructures display large magnetocaloric effect at temperatures below ∼10 K. While the maximum isothermal magnetic entropy change (ΔS _m ) value at 6 K is about −22.6 Jkg ^−1 K ^−1 for the Gd _2 O _3 nanorods and −17.8 Jkg ^−1 K ^−1 for Gd _2 O _3 nanoparticles for a magnetic field change of 70 kOe, the mixed Gd _2 O _3 nanosheets and nanorods system prepared by wet chemical method shows a maximum ΔS _m value of −23.6 Jkg ^−1 K ^−1 for the same field change. These are about 41% to 89% more than that of bulk Gd _2 O _3 . Therefore, Gd _2 O _3 -based nanostructures could be very useful for low temperature magnetic refrigeration applications.